(untitled) (Research, Society and Development, 2022)
This study aims to compare the safety culture between traditional care units and those aimed at COVID in a hospital in the South of Bahia. Cross-sectional study with 108 nursing professionals from traditional care units and those aimed at patients affected by COVID-19. For data collection, the Patient Safety Questionnaire in Hospitals (HSOPSC) was used. It was possible to show higher means in the COVID-19 units, for the dimensions “Teamwork within the units” (mean = 15.96 [± 1.15]); “Teamwork between hospital units” (mean = 14.80 [± 2.44]); “Internal transfers and shift change” (mean = 14.62 [±2.53]); and “Non-punitive error response” (mean = 8.89 [± 2.23]). In the dimension “General perception of patient safety” (mean = 14.14 [± 2.60]), in non-COVID-19 units the mean was higher. It can be seen then that the patient safety culture, despite still much to improve, proved to be better structured (strong) for different dimensions in the units that care for patients affected by COVID-19. Based on the positive results brought in these units, ways to implement such results in other sectors of the hospital unit should be sought.